Prevalence of cerebral palsy in Damanhur at Elbehera governorate - Noha Zidan Abdelwanees; Amany Muosa Mohamed; Eman Ibrahim elhadidy (Cairo : Noha Zidan Abdelwanees, 2017)
Back ground: Cerebral palsy (CP) is one of the most common causes of childhood physical disabilities. The prevalence rate of CP in developing countries is high. Purposes : To determine the prevalence of cerebral palsy in Damanhur at Elbehera Governorate. Subjects and Methods: One hundred sixty one children with CP receiving physical therapy services of both genders participated in this study. Their ages ranged from one month up to 14 years. They were recruited from two public hospitals, one private hospital and five private centers in Damanhur. They were subjected to modified Australian Registry Form. Results: within study population the results revealed that the prevalence of CP children who received physical therapy services was 0.8/ 1000 live birth in Damanhur. Boys and girls represented 39.1% and 60.9% respectively from total cases. Governmental hospital, private hospital and home represented 51.6,46.6 and 1.9 respectively. The percentage of CP types was spastic 88.2%, hypotonic 5%, dyskintic 4.9% and ataxic 1.9%.The results of Gross Motor Function Classification System (GMFCS) and Manual Ability Classification System .level IV and level V respectively had the highest percentages. and the results of Gross Motor Function Measure (GMFM)represented that less than one hundred was 46.6% from all percentages. Conclusion: Prevalence of CP in Damanhur city is high. Spastic type is the highest percentage while ataxic type is the least percentage of total cases . Based on GMFCS , MACS and GMFM, most of patients were severe cases
Thesis (M.Sc.) - Cairo University - Faculty of Physical Therapy - Department of Growth and Development Disorders in Pediatrics
Issued also as CD
Keywords: Cerebral Palsy; Damanhur; Prevalence